Quizziz y Quizlet como recursos didácticos para el aprendizaje de la asignatura de Biología Vegetal con estudiantes de tercer semestre de la carrera Pedagogía de las Ciencias Experimentales Química y Biología en el periodo mayo 2021- octubre 2021. - Sanaguano Fiallos, Joseline Esthefania (2022)
The present research work proposed the management of Quizziz and Quizlet as didactic resources for learning Plant Biology with third-semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology career. The problem was based on the fact that teachers do not use specialized didactic resources in learning the subject, but teaching is maintained in a traditional way. The design was non-experimental since the variables were not manipulated. Being Quizziz, Quizlet, and the learning of Plant Biology, the types of research were by their descriptive level, field location, and bibliographical. For the information and data collection, the survey technique was used, with the questionnaire as a structured instrument with ten questions that were applied to third-semester students. It was concluded Quizziz and Quizlet are didactic resources of academic support that allow the gamified participation of students. 90.6% consider very pertinent the elaboration of questionnaires with different types of questions such as tests, scatter, open answers. Checkboxes, etc., verification, flashcard, multiple choice workshops, fill in the blank, speller to examine and provide feedback on Plant Biology learning. They are also digital resources that benefit students as they allow them to relate the game to school activities.